DESIGN OF SHAFT, PULL AND V-BELT ON THE REAR WHEEL OF YAMAHA XEON GT 125CC MOTORCYCLE 2014 - Abdul Barr, Putranda Yedi (Jurusan Teknik Mesin, Universitas Halu Oleo, 2023)
Transportation is now a necessity for every human being. Therefore developments in the automotive sector, especially transportation, are increasing rapidly. Motorcycles are a combination of components whose number can reach more than a thousand parts. Motorcycles can run perfectly if all the components are in good condition. The components that are important on a motorcycle include wheels, tires and chains. For this reason, there are many things that must be considered by a designer in designing a motorcycle component, including adjusting a component according to its actual function, the safety factor of the planned component. , efficiency and cost factors. This study aims to identify and apply theoretical studies and compare the results of calculations with data from specifications in the form of designs, especially for transmission shafts, pulleys and v-belts on motorcycles. Based on the calculation results, it was found that the shaft diameter was 16.4 mm, the pulley diameter was 116.42 mm and the v-belt speed was 10.97 m/s and the v-belt length was 1073.32 mm. Keyword : Motorcycle, Design, Shaft, Pulley, V-belt